Comparative analysis of pulsed Nd:YAG laser welding of 304L and 904L stainless steel. (2020) - Kumar, Pramod; Sinha, Amar Nath
Abstract: The current study investigates the comparative study of similar pulsed Nd:YAG laser welding of 304L and 904L stainless steel. In the present study both austenitic stainless steel (304L) and super austenitic stainless steel (904L) are laser welded at 5 mm/s scanning speed, 25 Hz pulse frequency and 0.75 mm laser spot diameter. The ultimate tensile strength of both laser welded specimens were equal to the respective parent metals. The percent of ductility is more in 304L than 904L laser welded specimen comparatively. The weld bead shape of the two welded specimens are V shaped for 304L and H shaped for 904L at the same laser process parameters due to difference in thermophysical properties of the two materials.